The Neuromuscular Response of Patients With Multiple Sclerosis to Vibration Therapy - Asghar Tofighi; Saber Saedmocheshi; Ghafour Ghafari (University of Social Welfare & Rehabilitation Sciences, 2014)
Objectives: The purpose of this study is to examine the effect of whole body vibration on improvement of performance of patients with Multiple sclerosis.  Methods & Materials: In this study, 73 patients with MS a mean age of 73±2.63 years participated, out of which 20 patients took part with complete satisfaction. They had average disability ranging from 2.05 to 4.5. The subjects were divided into four groups based on Bosco plan: 1 control group and 3 experimental groups. The 1st group did their job in 6 sessions and within 6 weeks. The 2nd group did their job in 12 sessions and within 6 weeks and the last group in 18 sessions and within 6 weeks. The Vibration frequency was 15-25 Hz. Having finished the exercise, the neuromuscular function was assessed with the standard 5-chair and TUG test. In order to analyze the data,SPSS version 18 was used in level of significance of α=5.  Results: The results of repeated measures analysis of variance and one-way analysis of variance showed that the whole body vibration exercise significantly decreased the time of 5-chair test (P<0.03) and tug test (P<0.03). The 5-chair test with three sessions a week training exercise had significantly better neuromuscular function than the two other groups (P<0.04).  Conclusion: Whole-body vibration exercises in people with MS disease results in improvement of neuromuscular function.